Penerapan Latihan Kemampuan Positif pada Nn. Mp dengan Harga Diri Rendah di Ruangan Kabela Rumah Sakit Jiwa Prof. Dr. Vl. Ratumbuysang Provinsi Sulawesi Utara - Arruansilomba, Putri Pratiwi; Buanasari, Andi; Bidjuni, Hendro Joli Bidjuni (Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi, 2024)
Background: Low self-esteem is a significant issue that impacts psychological health. If not addressed promptly, low self-esteem can lead to persistent negative thoughts, potentially resulting in the loss of communication and functional abilities. Objective: To identify and train positive skills that are still present to support the enhancement of self-esteem in patients with schizophrenia. Method: A case study approach was used with nursing intervention involving positive skill training for patient Nn. MP. The intervention was implemented over a period of 9 days, with pre- and post-test measurements using the Self-Esteem Sorensen instrument to assess the outcomes of the intervention. Case Study Results: The case study revealed that pre- and post-test measurements using the Self-Esteem Sorensen instrument showed a decrease in scores related to agreement with negative statements, from 40 to 28. However, there was no change in the interpretation of the patient’s self-esteem, which remained very low. Conclusion: The patient was able to engage in the recommended positive activities according to the daily schedule, but the interpretation of the patient’s self-esteem remained very low. Nonetheless, there was a decrease in the score related to agreement with negative statements in the self-esteem questionnaire. Thus, the results of this case study can serve as a reference for future researchers to pay closer attention to the timing and stages of implementing strategies and to use interventions involving positive skill training that could improve self-esteem in patients with chronic low self-esteem schizophrenia. Keywords: Nursing care; Low self-esteem; Positive skills training.